Differences of Composition Operators on Bloch Type Spaces (Journal of Mathematical Study, 2018)
In 2007, T. Hosokawa and S. Ohno gave the sufficient and necessary conditionsof the boundedness and compactness of differences of composition operatorson the Bloch space. On this base, this paper will generalize these conditions of theboundedness and compactness of differences of composition operators on the Blochtype space.